Механизмы формирования оценочной семантики (на материале анализа перцептивных оппозиций) - Григорьева, Татьяна (Studia Rossica Posnaniensia, 2019)
This article discusses three models of the assessment value – functional, polyspherical and experiential. Drawing on the data within Russian explanatory dictionaries and texts containing language units of the opposition, represented in Russian National Corpus, the author describes the features of the presentation of these models, each of which has different contents value and different factors influencing the development of the evaluative semantics.